Irisin treatment improves healing of dystrophic skeletal muscle - Reza, Musarrat Maisha (2018)
Background: Irisin is an exercise induced myokine that is shown to promote browning of adipose tissue and hence, increase energy expenditure. Furthermore, our unpublished results indicate that Irisin improves myogenic differentiation and induces skeletal muscle hypertrophy. Since exercise induced skeletal muscle hypertrophy improves muscle strength, we wanted to investigate if ectopic injection of Irisin peptide improves skeletal muscle function in a mouse model of muscular dystrophy. This utility of Irisin peptide is yet to be studied in animal models. Methods: In order to test this hypothesis, we expressed and purified recombinant murine Irisin peptide from E. coli. Three- to six-week-old male mdx mice were injected IP with either vehicle (dialysis buffer) or Irisin recombinant peptide for two or four weeks, three times-a-week. Results: Irisin injection increased muscle weights and enhanced grip strength in mdx mice. Improved muscle strength can be attributed to the significant hypertrophy observed in the Irisin injected mdx mice. Moreover, Irisin treatment resulted in reduced accumulation of fibrotic tissue and myofiber necrosis in mdx mice. In addition, Irisin improved sarcolemmal stability, which is severely compromised in mdx mice. Conclusion: Irisin injection induced skeletal muscle hypertrophy, improved muscle strength and reduced necrosis and fibrotic tissue in a murine dystrophy model. These results demonstrate the potential therapeutic value of Irisin in muscular dystrophy.